POSITIVE PERSONALITY TRAITS OF THE MAIN CHARACTER SIMBA IN THE LION KING FILM - Josephine Natasya Rianggi; Devi Hellystia (Universitas Gunadarma, 2023)
This research aims at finding and analyzing positive personality traits in the maincharacter Simba in The Lion King film. This research used a qualitative research method, which the data are interpreted and described narratively. The data of thisresearch are taken from the dialogues of the scene where the positive personality traits ofSimba as the main character are shown. This research applied positive personality traits proposed by Lauther (2012). The results of this research show there are 26 data ofpositive personality traits. They are classified into six positive personality traits comprise;Love (6 data), Friendship (4 data), Honesty (5 data), Responsibility (4 data), Courage (5data) and Loyalty (2 data). However, other six positive personality traits are not found inthe scene. They are Respect, Adaptability, Compatibility, Resolution, Compassion, andPatience.